Mengurangi perilaku impulsif pada anak attention-deficit hyperactivity disorder dengan teknik reprimand dan token economy - Faizah Faizah (Universitas Muhammadiyah Malang, 2022)
One of the dominant symptoms of Attention-Deficit Hyperactivity Disorder (ADHD) is the presence of impulsive behavior which is a condition of failure to control impulses to take certain actions. The assessment methods used were clinical interviews, observation, The Wechsler Intelligence Scale for Children (WISC) and Indonesian ADHD Rating Scale (IARS) tests. The intervention provided is behavior modification with reprimand and token economy techniques to reduce the behavior of taking other people’s goods without permission and forming behavior asking for permission. The results of the intervention showed a decrease in the subject’s impulsive behavior and the formation of new behavior, namely asking for permission